2020
DOI: 10.1039/c9nj05042f
|View full text |Cite
|
Sign up to set email alerts
|

Azilsartan piperazine salt solvate and monohydrate: preparation, crystal structure, enhanced solubility and oral bioavailability

Abstract: Two azilsartan–piperazine salt solvates and a monohydrate feature crystal structural diversity and improve the azilsartan solubility over that of the free Az form. Az–Pz·EtOH and Az–Pz·H2O improve the plasma azilsartan concentration Cmax and AUC over the free Az form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…46−52 Therefore, the higher solubility of FPV-PP might be a result of the higher solubility of PP. 53,54 On the other hand, as shown in Figure S3, the special crystal structure of the FPV-PP salt has many cavities, with the primary hydrophilic amino groups stretching inward. 55,56 Due to the solvent inclusion of cavities and their internal hydrophilic environment, the solubility of the FPV-PP salt has been enhanced in comparison with that of FPV.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…46−52 Therefore, the higher solubility of FPV-PP might be a result of the higher solubility of PP. 53,54 On the other hand, as shown in Figure S3, the special crystal structure of the FPV-PP salt has many cavities, with the primary hydrophilic amino groups stretching inward. 55,56 Due to the solvent inclusion of cavities and their internal hydrophilic environment, the solubility of the FPV-PP salt has been enhanced in comparison with that of FPV.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The solubility of the FPV-PP salt was significantly improved by 1.6-fold in comparison with that of FPV. Many examples have also shown that the solubility of drug salts could be effectively improved due to the higher solubility of the salt-forming reagent. Therefore, the higher solubility of FPV-PP might be a result of the higher solubility of PP. , On the other hand, as shown in Figure S3, the special crystal structure of the FPV-PP salt has many cavities, with the primary hydrophilic amino groups stretching inward. , Due to the solvent inclusion of cavities and their internal hydrophilic environment, the solubility of the FPV-PP salt has been enhanced in comparison with that of FPV . Above all, the higher solubility of FPV-PP salt might be a result of the high solubility of PP, the special cavity structure of the salt, or both.…”
Section: Resultsmentioning
confidence: 99%
“…PXRD performs as an effective tool to judge the solid-substance states, including salt, polymorphs, and physical mixture, and check the phase purity of the bulk samples based on the line profile. , The PXRD patterns of seven HAM salts (experimental-exp and simulation-sim), HAM, and the corresponding acidic counterions are shown in Figure S1­(a–g). It can be seen that the PXRD patterns of prepared HAM salts were different from that of either HAM or acidic counterions, indicating that the new solid forms were produced.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the piperazine ring is considered an important class of nitrogen heterocycles that can effectively regulate the lipid-water partition coefficient and acidbase equilibrium constants of drugs, which may have positive influences on improving the druggability of DAI [25]. What is more, a series of the literature on the cocrystals with PPZ demonstrates that the introduction of PPZ can significantly optimize the solubility and bioavailability of active pharmaceutical ingredients (APIs) [24,26,27]. Until now, there have been some studies on the cocrystal of DAI reported [14,28,29].…”
Section: Introductionmentioning
confidence: 99%